Essays on Language and Ethnic Relations - Abdul Karim Abdullah @ Leslie Terebessy; Nabila Yusof @ Abdul Rahman; Hisham Sabri (Pusat Pengajian Umum, Universiti Sains Islam Malaysia, 2022)
This book has a lot of benefit to increase a new knowledge. The content is related to issues in generating new finding in language and ethnic relation. Most of the topic being approach with Islamic Principle. The topic discussed the issue related to intercultural conflict management, motivational orientation, languages human capital and ethnic relation.